2010
DOI: 10.1093/nar/gkq294
|View full text |Cite
|
Sign up to set email alerts
|

The RNA binding protein Larp1 regulates cell division, apoptosis and cell migration

Abstract: The RNA binding protein Larp1 was originally shown to be involved in spermatogenesis, embryogenesis and cell-cycle progression in Drosophila. Our data show that mammalian Larp1 is found in a complex with poly A binding protein and eukaryote initiation factor 4E and is associated with 60S and 80S ribosomal subunits. A reduction in Larp1 expression by siRNA inhibits global protein synthesis rates and results in mitotic arrest and delayed cell migration. Consistent with these data we show that Larp1 protein is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
118
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(132 citation statements)
references
References 33 publications
12
118
0
Order By: Relevance
“…In animals, LARP1s are mainly cytoplasmic proteins that function in metabolism of specific mRNAs. LARP1 formed a complex with PABP and eIF4E and was localized to P-bodies, where mRNA decay occurs (Blagden et al, 2009;Burrows et al, 2010;Chauvet et al, 2000;Ichihara et al, 2007;Nykamp et al, 2008;Singh et al, 2011). Furthermore, LARP1 is involved in cellular remodeling, migration, and apoptosis (Burrows et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In animals, LARP1s are mainly cytoplasmic proteins that function in metabolism of specific mRNAs. LARP1 formed a complex with PABP and eIF4E and was localized to P-bodies, where mRNA decay occurs (Blagden et al, 2009;Burrows et al, 2010;Chauvet et al, 2000;Ichihara et al, 2007;Nykamp et al, 2008;Singh et al, 2011). Furthermore, LARP1 is involved in cellular remodeling, migration, and apoptosis (Burrows et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…LARP1 formed a complex with PABP and eIF4E and was localized to P-bodies, where mRNA decay occurs (Blagden et al, 2009;Burrows et al, 2010;Chauvet et al, 2000;Ichihara et al, 2007;Nykamp et al, 2008;Singh et al, 2011). Furthermore, LARP1 is involved in cellular remodeling, migration, and apoptosis (Burrows et al, 2010). Deletion of LARP1 leads to developmental defects during spermatogenesis in D. melanogaster (Blagden et al, 2009;Ichihara et al, 2007) and oogenesis in C. elegans (Nykamp et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we found that PDGFRα was strongly down-regulated in both OLs and type II astrocytes, suggesting that PDGFRα is also a key factor in maintaining self-renewal and inhibiting differentiation of OPCs. Transcription factors (TFs) and binding proteins play prominent roles in developmental processes and cell-lineage specification (Ahmed et al 2009;Burrows et al 2010). Here, we found that many OPC-expressed TFs and binding proteins, such as E2F transcription factor 8, pituitary tumortransforming 1 and cell division cycle 20 homolog, were down-regulated in both OLs and type II astrocytes, suggesting they may be involved in maintaining proliferation and self-renewal of OPCs.…”
Section: Gene Profiles Of Opcsmentioning
confidence: 95%